CHANGES IN ATPASE AND PHOSPHATASES IN DIFFERENT TISSUES OF CRAB, OZIOTELPHUSA SENEX SENEX, FOLLOWING EXPOSURE TO FENVALERATE - KALPANA PANATI; VENKATA R. NARALA; VENKATRAMANA REDDY ARVA TATIREDDIGARI (The Bioscan, 2012)
The changes in Na+-K+-ATPase, Mg2+-ATPase and Acid phosphatase and Alkaline Phosphatase in the Central Nervous System (CNS) and Pedipalpal Muscle (PM) of Crab, Oziotelphusa senex senex following ambient exposure to sublethal concentration of Fenvalerate have been studied. The changes in ATPase and Phosphatase systems at different time intervals like 3, 6, 12, 24 and 48h following exposure have been studied. We found that ATPase activity was inhibited in both CNS and PM with maximum effect at 12h after exposure. In contrast, phosphatase system was elevated at all time periods with greater changes at 24h after exposure to Fenvalerate. Thereafter, changes in ATPase and phosphatase system showed recovery tendency by 48h, suggesting operation of detoxification mechanisms on one hand and possible biodegradation of fenvalerate in the animal system.